2012
DOI: 10.1002/adem.201200160
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic Iron Foams – On Deformation Mechanisms and Strain‐Rate Dependence of Compressive Properties

Abstract: Using hollow particles as reinforcement, syntactic foams are a unique class of materials with features of conventional foams as well as composites. Usually, the main role of the filler is to introduce porosity, and thus also change specifically the compressive response to that of a typical foam or cellular material. However, depending on which of the many variants of such syntactic foams is considered, hollow particles can also have a strengthening effect. In the way this is achieved, however, they are disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…In particular, the strain-rate sensitivity response at three different strain rate levels was studied by taking into account the influence of type and volume fraction of glass spheres. The materials' behaviour was found to be very similar to that of the metal matrix [2,[6][7][8]. Castro and Nutt produced steel based MMSFs, filled with ceramic hollow spheres by gravity fed and mechanical pressure infiltration.…”
Section: Introductionmentioning
confidence: 87%
“…In particular, the strain-rate sensitivity response at three different strain rate levels was studied by taking into account the influence of type and volume fraction of glass spheres. The materials' behaviour was found to be very similar to that of the metal matrix [2,[6][7][8]. Castro and Nutt produced steel based MMSFs, filled with ceramic hollow spheres by gravity fed and mechanical pressure infiltration.…”
Section: Introductionmentioning
confidence: 87%
“…Peroni et al [59,60] investigated the mechanical behaviour of MMSFs made of hollow glass spheres mixed in iron matrix. The produced materials offered greatly increased quasi-static compressive strength, though at higher density.…”
Section: Introductionmentioning
confidence: 99%
“…[10,[12][13][14][15][16][17][18][19][20] Dynamic properties of syntactic foams are affected by the geometry and volume fraction of hollow microspheres. [13][14][15][16] The treatment of hollow microspheres can improve their interfacial adhesion to the epoxy matrix and thus the impact properties of the bulk foam, especially the strength. [10] Pellegrino et al reported the glass microballoon polyurethane syntactic foam possesses higher strain rate sensitivity in tension compared to compression.…”
mentioning
confidence: 99%